Розроблення й впровадження перспективних методів розрахунку і моделювання при проектуванні та експлуатації потужних турбогенераторів та гідрогенераторів для ТЕС, АЕС, ГЕС, ГАЕС - Кобзар, Костянтин Олександрович; Третяк, Олексій Володимирович; Шуть, Олександр Юрійович; Полієнко, Владислав Русланович; Гакал, Павло Григорович; П'ятницька, Євгенія Святославівна (НТУ "ХПІ", 2018)
Вперше в Україні (не має аналогів) на світовому рівні з використанням розробленої методики проведено розрахункові дослідження з проектування й моделювання потужних турбо- та гідрогенераторів. Це дозволило створити енергетичні установки нового покоління з показниками ефективності та надійності, які відповідають світовим вимогам, що пред'являються до енергетичного устаткування. Побудовано турбогенератор ТГВ-550-2МУ3 та розроблено технічні умови для його впровадження на Екібастузській ДРЕС. Спроектовано та розроблено гідрогенератор-двигун СВО2-1255/255-40 УХЛ4 з метою впровадження на Дністровській ГАЕС.

For the first time in Ukraine (there is no analogues) at the world level, using the designed methods, calculation researches were carried out on designing and simulation of high power Turbogenerators and Hydrogenerators. This let design power plants of a new generation with indices of efficiency and reliability that meet the world requirements that are submitted to the power equipment. Turbogenerator TGV-550-2MU3 (rated 550 MW) was manufactured and technical specifications for its put in to operation at Ekibastuzskaia SDPP were designed. In accordance with the requirements of GOST 533-2000 for Turbogenerators rated over 350 MW mean time between failures comprises 18000 h., that corresponds to complete specified service life of 40 years. Given condition in the complete scope is provided for Turbogenerator TGV-550-2MU3, the stand tests were carried out successfully. Hydrogenerator-Motor SVО2-1255/255-40 UHL4 (power in the generator mode is of 324 MW, power of the motor is of 416 MW) was designed with the purpose of put in to practice at Dniestrovskaya HPSP. Taking in to consideration the necсesity of trouble-free operation of the hydroaggregate during long term at provision of peak loads of the electric power net for all the parts the calculations of complex stressed state which let develop the design corresponding to the best world standards were carried out. Designed Turbogenerators and Hydrogenerators give possibility to expand the export opportunities of the power enterprises of our state, which makes a significant contribution in to the economic development of the country.
Development and implementation of promising methods and model engineering during the design and operation of powerful turbogenerators and hydrogenerators
Keywords: бандажне кільце ротору; торсійний вал; втомне руйнування; складнонапружений стан; убмікротріщина; мікротріщина; міцність; turbogenerator; retaining ring of the rotor; torsion shaft; fatigue distorsion; complex stressed state; simulation; submicro crack; micro crack; strength